2022
DOI: 10.1109/jlt.2022.3176921
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Polarization Optical Correlation-Domain Reflectometry (POCDR)

Abstract: We propose a new scheme for polarization-sensitive distributed fiber-optic sensing, called polarization optical correlation-domain reflectometry (POCDR), and experimentally demonstrate its fundamental operations. In this scheme, the states of polarization (SOPs) of reference lights are controlled so that they are uniformly distributed on the Poincaré sphere using a calibration method, which cancels the effect of unknown birefringence in the fibers used in the system. Then the SOP of spontaneous Brillouin scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…To date, no technique (except for the one we have developed) has been reported that enables low-cost temperature measurement near the tip of a commercially available optical fiber without necessitating any specialized processing. Alternatively, distributed sensing techniques capable of providing longitudinal temperature variations along the fiber have been explored, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but these too come with a high cost.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no technique (except for the one we have developed) has been reported that enables low-cost temperature measurement near the tip of a commercially available optical fiber without necessitating any specialized processing. Alternatively, distributed sensing techniques capable of providing longitudinal temperature variations along the fiber have been explored, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but these too come with a high cost.…”
mentioning
confidence: 99%
“…Brillouin-based single-end-access distributed sensors can be categorized into three types: Brillouin optical time-domain reflectometry (BOTDR), [12][13][14] Brillouin optical frequency-domain reflectometry (BOFDR), 15) and BOCDR. [16][17][18][19][20][21][22][23][24][25][26] Each technique has its own merits and demerits, and here we focus on BOCDR.…”
mentioning
confidence: 99%
“…2) Various distributed sensing techniques have been developed and can be categorized into two types: analyzers, which require light injection at both ends of the FUT to induce stimulated Brillouin scattering, [4][5][6][7][8][9][10] and reflectometers, which rely on spontaneous Brillouin scattering by injecting light at only one end of the FUT. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] These techniques are further differentiated by their spatial resolution capabilities, categorized into time, [4][5][6][7][11][12][13] frequency, 8,14) and correlation domains. 9,10,[15][16][17][18][19][20][21][22][23][24] This study specifically examines Brillouin optical correlation-domain reflectometry (BOCDR), [15][16][17][18...…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24] These techniques are further differentiated by their spatial resolution capabilities, categorized into time, [4][5][6][7][11][12][13] frequency, 8,14) and correlation domains. 9,10,[15][16][17][18][19][20][21][22][23][24] This study specifically examines Brillouin optical correlation-domain reflectometry (BOCDR), [15][16][17][18][19][20][21][22][23][24] which utilizes correlation control of continuous lightwaves within a selfheterodyne setup. BOCDR is distinguished by its ability to operate with single-end light injection, offering relatively high spatial resolution, high sampling rates, random accessibility, and cost efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation